Environmental Policies and Strategic Communication in Iran : The Value of public Opinion Research in Decisionmaking - Calabrese, Daniele; Kalantari, Khalil; Santucci, Fabio M.; Stanghellini, Elena (Washington, DC : World Bank, 2012)
Iran is currently implementing a five-year project, co-financed by the World Bank, aims: a) to strengthen the institutional capacity to monitor air and water quality, b) to build partnerships among ministries, universities, municipalities and civil societies, and c) to strengthen training and public awareness on environmental issues. These studies reveal some factors such as age and education are consistently related to environmentalism over time and across studies. This publication reports the main findings of a survey conducted on the perception, knowledge, and behavior of Tehran residents, relating to the environment. The study confirms the need for a properly focused information campaign to raise the level of knowledge about the environment and to form the consciousness that could motivate people to act or to accept the changes imposed by the authorities. The study also found several information channels need to be used in order to reach different groups of Tehran residents.